Large Vertex Encephaloceles: Management and Outcomes. Issue 1 (9th January 2023) - Schneider, Hoa; Cappitelli, Alex; Langa, Olivia C.; Goobie, Susan M.; Meara, John G.; Proctor, Mark; Ganske, Ingrid M.
Abstract : Background: Complex vertex and posterior encephaloceles containing brain tissue have uncertain prognosis and high operative risk. Patients may not be offered operative intervention depending on local and regional specialist expertise. The authors present their experience treating 5 such pediatric patients. Methods: This is a retrospective review of the surgical assessment, planning, and technique of cranial repairs, as well as surgical outcomes and developmental follow-up regarding adaptive functioning for patients presenting for second opinion for encephalocele of the cranial vertex after having been deemed too high risk at another institution. Results: Five consecutive patients presented between January 2014 and June 2016. One patient was not offered repair. Of 4 patients who underwent reconstruction, average age at time of repair was 2.7 months (range, 0.9–6.7). One presented with ruptured encephalocele, whereas the remaining 3 underwent drainage of the encephalocele (average volume of 1200 mL) at time of surgical resection. Operative time averaged 3.7 hours (range, 2.2–5.3). There were no deaths. One patient had a single seizure postoperatively. Two patients required placement of permanent shunt for hydrocephalus. Two patients completed developmental evaluations, both of whom exhibited delays in adaptive functioning relative to same-aged peers. Conclusions: Patients with large, complex encephalocele warrant evaluation by an experienced high-volume tertiary care pediatric craniofacial center. The decision to proceed with surgical management should include an interdisciplinary team of surgeons, anesthesiologists, neurologists, and social work. Further study of developmental outcomes in both operated and unoperated patients is necessary to better understand risks and benefits of reconstruction.